Brachial artery thrombosis in a dog causing monoparesis mimicking nerve sheath tumor. (13th July 2021) - Andruzzi, Melissa N.; Voges, Andra K.; Russell, Karen E.; Jeffery, Nick D.
Abstract: There are few differential diagnoses for non‐orthopedic thoracic limb lameness in adult dogs aside from nerve tumors and disk‐associated nerve compression; this report introduces another etiology. A 9‐year‐old male castrated mixed dog presented with an episodic history of nonweight‐bearing thoracic limb lameness. Additional clinical signs included an atrophied thoracic limb with cool paw pads and painful axillary region. Magnetic resonance imaging, computed tomography, ultrasound, and exploratory surgery confirmed a chronic thrombus of the right brachial artery. No underlying cause for the thrombus was identified. The dog has been successfully managed on long‐term rivaroxaban and clopidogrel. Follow‐up ultrasound of the thrombus suggested early remodeling.